2012
DOI: 10.3389/fimmu.2012.00087
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic H1N1 Influenza Infection and Vaccination in Humans Induces Cross-Protective Antibodies that Target the Hemagglutinin Stem

Abstract: Most monoclonal antibodies (mAbs) generated from humans infected or vaccinated with the 2009 pandemic H1N1 (pdmH1N1) influenza virus targeted the hemagglutinin (HA) stem. These anti-HA stem mAbs mostly used IGHV1-69 and bound readily to epitopes on the conventional seasonal influenza and pdmH1N1 vaccines. The anti-HA stem mAbs neutralized pdmH1N1, seasonal influenza H1N1 and avian H5N1 influenza viruses by inhibiting HA-mediated fusion of membranes and protected against and treated heterologous lethal infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
106
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(122 citation statements)
references
References 51 publications
16
106
0
Order By: Relevance
“…Our study has confirmed that staining and sorting peripheral B cells with soluble HA can greatly enrich for virus HA-specific clones (19,23). This enabled us to analyze a large sample of monoclonal antibodies from a single individual, for which heavy and light chains and function could be assigned.…”
Section: Discussionmentioning
confidence: 62%
“…Our study has confirmed that staining and sorting peripheral B cells with soluble HA can greatly enrich for virus HA-specific clones (19,23). This enabled us to analyze a large sample of monoclonal antibodies from a single individual, for which heavy and light chains and function could be assigned.…”
Section: Discussionmentioning
confidence: 62%
“…First, we demonstrate that H7 cross-reactive antibodies induced by vaccination with H1N1 or H3N2 influenza A strains are not uncommon. Previous studies have shown that broadly reactive antibodies binding to the HA stalk region are relatively rare (25), but they were preferentially induced by exposure to the highly unique 2009 pandemic H1N1 strain (16,26,27). It was hypothesized that exposure to this pandemic strain, which has a globular head domain that is highly divergent from prepandemic seasonal H1N1 strains, was activating cross-reactive memory B cells reactive with conserved epitopes (e.g., in the stalk region) that the virus shared with previous seasonal strains (2, 28).…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected from individuals treated for IPAP. Individual memory B cells binding to GM-CSF were sorted into individual wells (55) (Fig. S6).…”
Section: Methodsmentioning
confidence: 99%